Access, Fronthaul and Backhaul Networks for 5G & Beyond - Imran, Muhammad Ali; Zaidi, Syed Ali Raza; Shakir, Muhammad Zeeshan (Telecommunications, 2017)
The widespread use of mobile internet and smart applications has led to an explosive growth in mobile data traffic, which will continue due to the emerging need of connecting people, machines, and applications in an ubiquitous manner through the mobile infrastructure. The efficient and satisfactory operation of all these densely deployed networks hinges on a suitable backhaul and fronthaul provisioning. The research community is working to provide innovative technologies with extensive performance evaluation metrics along with the required standardisation milestones, hardware and components for a fully deployed network by 2020 and beyond. Access, Fronthaul and Backhaul Networks for 5G & Beyond provides an overview from both academic and industrial stakeholders of innovative backhaul/fronthaul solutions. Covering a wide spectrum of underlying themes ranging from the recent thrust in edge caching for backhaul relaxation to mmWave-based fronthauling for radio access networks, this book is essential reading for engineers, researchers, designers, architects, technicians, students and service providers in the field of networking, mobile and wireless and computing technologies working towards the deployment of 5G networks.